Common Patterns in Chaperone Interactions with a Native Client Protein. Issue 20 (17th April 2018) - He, Lichun; Hiller, Sebastian
Abstract: Many molecular chaperones are promiscuous and interact with a wide range of unfolded, quasi‐native, and native client proteins. The mechanisms by which chaperones interact with the highly diverse structures of native clients thus remain puzzling. In this work, we investigate at the atomic level how three ATP‐independent chaperones interact with a β‐sheet‐rich protein, the Fyn SH3 domain. The results reveal that the chaperone Spy recognizes the locally frustrated surface of the client Fyn SH3 and that the interaction is transient and highly dynamic, leaving the chaperone‐interacting surface on Fyn SH3 solvent accessible. The two alternative molecular chaperones SurA and Skp recognize the same locally frustrated surface of the Fyn SH3 domain. These results indicate dynamic recognition of frustrated segments as a common mechanism underlying the chaperone–native client interaction, which also provides a basis for chaperone promiscuousness. Abstract : Blurred lines : Molecular chaperones recognize frustrated surfaces on native client proteins regardless of their sequence and structure. Multi‐conformational fuzzy complexes form through transient interactions, thereby enabling chaperone–client interactions in the absence of structural complementarity and circumventing steric hindrance.